REPRESENTATIONS AND STRATEGIES FOR THE DEVELOPMENT OF COMPETENCES OF PROFESSIONALS OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2017)
The current demands of the competitive job market are challenging, demand quality and professional competence invarious fields. In the context of physical education to search actions and methods to enhance the performance and skills at work, canbe decisive for the professional and organizational success. This study aims to analyze the representations of faculty of St. LouisUniversity on professional competence and their development strategies and specifically identify the professional competence ofrepresentation for university teachers; verify the perception of the main characteristics of a competent professional; analyze themain strategies for the development of professional skills. The research is qualitative and exploratory. It had as a date collection toolsemi-structured interviews with open questions. Held in the first week of November 2015, at the University CEUMA. The sampleconsists of two teachers and two teachers of a particular University of St. Louis, among teachers with 54 years old and the other 45years, the teachers a 39-year and the other 34 years. It was concluded that the professional competence representations in highereducation relate to the commitment, knowledge, appropriate methodologies, qualification and success in what you do. And thestrategy used for professional qualification is the career planning the search for knowledge through continuing education.